Peran Pusat Pembelajaran Keluarga (Puspaga) Kota Surabaya Dalam Ketahanan Keluarga - Maharani, Cecilia Raisadina; Kurniawan, Bagus Ananda (Peneliti.net, 2024)
The increasing divorce rate in Surabaya is one of the problems that must be addressed immediately. So, there needs to be an effort to anticipate and solve problems in the family, the first step that can be done is to provide insight and education through the family development program by the Surabaya City Family Learning Center (PUSPAGA). Various services are provided by the Surabaya City Family Learning Center (PUSPAGA) as an effort to help strengthen family resilience. The purpose of this study is to describe the role of the Family Learning Center (PUSPAGA) and analyze the supporting and inhibiting factors. This type of research is descriptive qualitative with two data collection techniques, namely interviews and documentation. The results showed that the Surabaya City Family Learning Center (PUSPAGA) can provide the role of family development through strengthening the components of family resilience and the main priority program of PUSPAGA is counseling activities. The psychological resilience of a family is given more attention by PUSPAGA, because it affects the improvement of a person's skills in running his life which is then related to mental health. If the family's psychological resilience goes well, then the other components of family resilience also receive a positive impact, because the components of physical, social and psychological resilience are interrelated with each other. However, in its implementation, there are still obstacles such as the lack of enthusiasm from the community and the lack of optimal socialization of the service program.